Effect Of Workplace Incivility On The Job Burnout Among The Employees Of National Bank 0f Pakistan In Sukkur Region - Chakar, Muhammad; Haque, Raheela; Chuadhry, Muhammad Asif; Shaikh, Hisam uddin; Khaskheli, Ghulam Akbar; Shaikh, Saifullah; Abbas, Qamar (Migration Letters, 2024)
The aim of this research was to examine the influence of workplace incivility on job burnout through various aspects. Data was obtained from 125 employees of the National Bank of Pakistan located in the Sukkur area using a questionnaire. The results showed that workplace incivility has a detrimental effect on employee performance and leads to burnout. The employees experience incivility in various forms such as physical-verbal, active-passive, and direct-indirect. This incivility not only leads to employee turnover but also impacts the organization’s performance. The study concludes that workplace incivility has a significant negative impact on organizations. Recommendations for further research are also provided.